The relationship between non-performing loans, banking system stability and economic activity: The case of Tunisia - Dorsaf Elbir Merhbene (Graduate Institute of International and Development Studies, 2021)
This study seeks to determine the relation between non-performing loans (NPLs) and bank profitability in Tunisia. This relation appears non-linear. We estimate a threshold of NPLs using an econometric framework. We examine the determinants affecting profitability over the Q4 2010 - Q4 2019 period for 10 Tunisian banks by estimating a model showing the impact of NPLs on bank profitability. The results indicate that banks with lower non-performing loan tend to have higher profitability.
Keywords: 330; NPLS; banking profitability